ANALISIS SISTEM PENGENDALIAN INTERN DALAM PEMBERIAN KREDIT PADA PT.BANK RAKYAT INDONESIA (PERSERO) CABANG SIDENRENG RAPPANG - K, Rikayanti (DECISION : Jurnal Ekonomi dan Bisnis, 2021)
This research purposed to analyzing the internal control system in providing credit at PT. Bank Rakyat Indonesia (Persero) Cabang Sidenreng Rappang. Is the internal control system implemented according to the intern of control elements according to COSO. The research data collection techniques through observation and interviews. The data analysis used is a qualitative method. The results showed that the provision of credit at PT BRI Cabang Sidenreng Rappang was carrying to based on a written application letter signed by the applicant. The credit application is written by in a form provided by the bank. Deskman or Customer Service is in charge of handling customer credit applications. Credit requirement documents in the form of customer financial reports. This document will use as a reference for the customer's business prospects.